Wellbore failure during water-alternating-gas injection by use of flow-stress coupling method - Bataee, M. (Society of Petroleum Engineers, 2017)
Accurate evaluation of failure pressure is crucial in the design of injection wells. Besides, in-situ stresses play an important role in obtaining the results. Pressure and rock stresses are related together as the role of effective-stress theorem. In fact, pressure changes with stress alteration caused by change in porosity and permeability. Therefore, it should be obtained with the coupling method. Moreover, to calculate pressure, temperature, and stress in the fully coupling method, a huge matrix should be solved, and it takes long processing time to implement it. Therefore, this study developed a wellbore geomechanical model for stability during injection by use of the iterative coupling method. The processing speed was enhanced in this study because the parameters were calculated separately. The parameters of pressure, temperature, saturation, and stress were obtained for the multiphase-flow condition with numerical modeling. Furthermore, in this study, the finite-difference method (FDM) had been used to solve pressure, temperature, and saturation, whereas the finite-volume method (FVM) was applied to solve the wellbore stress. On top of that, the iterative coupling method was used to improve the accuracy of the stress results. As a result, a correction of approximately 20 psi (0.14 MPa) was noted for pressure in relation to stress, which is 1 psi (6.89 kPa). Moreover, the Drucker-Prager failure criterion was used to model the fracturing on the basis of the stress results. Other than that, sensitivity analysis on horizontal maximum (o-H) and minimum (o-h) stresses showed that by increasing O-H, the maximum injection pressures to avoid fracturing had been reduced, whereas in the case for O-h, an increment was observed. Copyright © 2017 Society of Petroleum Engineers.